Comparison between two statistics to test the hypothesis of equality of regression coefficients - Ruy Porto de Carvalho, José (Pesquisa Agropecuaria Brasileira, 1998)
In this paper, the Likelihood Ratio Test is presented to test the hypothesis of equality of regression coefficients. It is compared through simulated and experimental results with the largelly recommended t' statistics. Their comparison shows that the Likelihood Ratio Test may be used as a general procedure to test this type of hypothesis. It showed a great observed power in the different experimental situations used.